Coronavirus Infection and BCG Vaccination: Facts and Possibilities - B. V. Karalnik; B. I. Alimbekova; L. T. Eralieva (Эпидемиология и вакцинопрофилактика, 2020)
Relevance. The relevance of protection against SARS-Cov-19 by means of BCG vaccination is important not only with respect to coronavirus infections. That issue should be considered in light of overall biological and immunological pillars (innate immunity system).Aims. To consider the role of the lipid components and certain vaccines in stimulation of the innate immunity system, in particular, in induction of the heterogenous immune response and protection against various pathogens, including Covid-19, based on analysis of known scientific facts.Conclusions. The relevant database has been analyzed (51 scientific publications), including studies with application of various methods from immunological tests (in vitro and in vivo) to epidemiological trials. The analysis revealed the meaningful potential of heterogenous protection against various infections by means of BCG immunization, and according to some data, measles vaccine capacity. Simultaneously on the basis of performed analysis, the following issues that so far remained unclear have been identified: what is the duration of heterogenous protection; what is the optimal timing for BCG administration as related to the outbreak period of dangerous infection for the sake of decrease of its harm. The analyzed materials of that review substantiate the rationale for further continuation of the scientific studies and possibility for application of already accumulated data in order to protect, primarily the risk groups, against dangerous infections, especially in the timeframe when no relevant vaccines are available. Besides, the conducted review serves as the leverage for expected development of the new preventive medicine dimension – the systemic vaccine prophylaxis.